2016
DOI: 10.1007/s00464-016-4835-8
|View full text |Cite
|
Sign up to set email alerts
|

Impact of totally laparoscopic combined management of colorectal cancer with synchronous hepatic metastases on severity of complications: a propensity-score-based analysis

Abstract: TLA for combined resections is feasible, and its indications can be widened to encompass a larger population of patients, provided its benefits in terms of reduced overall risk and severity of complications, rapid functional recovery and favorable long-term outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 43 publications
(97 reference statements)
1
37
1
Order By: Relevance
“…64 e 2016AustraliaPropensity scoreLLR14663.05NANANAPartial36NA5OLR14061.35NANANAHLR andhybridRatti et al . 65 e 2016ItalyPropensity scoreLLR2560 (37–80)14/112.9 (0.5–11)2 (1–6)LLR37 (15–75)1 (4)5OLR5062 (35–81)27/233.4 (0.9–12)2 (1–7)Tranchart et al . 66 e 2016JapanPropensity scoreLLR8966.6 ± 10.847/422.9 ± 1.91.4 ± 0.6Partial26 (1–94)6 (7)5OLR8965.0 ± 9.449/402.8 ± 2.01.5 ± 0.7HLR26 (1–100)Untereiner et al .…”
Section: Resultsmentioning
confidence: 99%
“…64 e 2016AustraliaPropensity scoreLLR14663.05NANANAPartial36NA5OLR14061.35NANANAHLR andhybridRatti et al . 65 e 2016ItalyPropensity scoreLLR2560 (37–80)14/112.9 (0.5–11)2 (1–6)LLR37 (15–75)1 (4)5OLR5062 (35–81)27/233.4 (0.9–12)2 (1–7)Tranchart et al . 66 e 2016JapanPropensity scoreLLR8966.6 ± 10.847/422.9 ± 1.91.4 ± 0.6Partial26 (1–94)6 (7)5OLR8965.0 ± 9.449/402.8 ± 2.01.5 ± 0.7HLR26 (1–100)Untereiner et al .…”
Section: Resultsmentioning
confidence: 99%
“…In consideration of the influence of adjuvant chemotherapy on the overall survival and disease-free survival, the administration of postoperative chemotherapy was comparable between the laparoscopic and open groups in nine studies, while the remaining three studies [ 21 , 24 , 25 ] did not report the details about postoperative chemotherapy. Therefore, we did a sensitivity analysis by removing those three studies, and the results were consistent with original outcomes (overall survival: 1 year, 0.54 (95% CI 0.16–1.59; 5 years, 0.66 (95% CI 0.16–2.69); disease-free survival: 1 year, 1.31 (95% CI 0.50–3.41); 3 years, 0.80 (95% CI 0.34–1.86)).…”
Section: Resultsmentioning
confidence: 99%
“…However, the intraoperative blood loss was less in the MIS group than in the OS group (WMD = -130.09, 95%CI: -210.95 to -49.23, P = 0.002, I 2 = 91% for heterogeneity, P < 0.00001; Figure 2B). Seven studies reported the number of intraoperative blood transfusions in 407 patients[24-27,29-31]. The number of intraoperative blood transfusions was significantly less in the MIS group than in the OS group (OR = 0.53, 95%CI: 0.29 to 0.95, P = 0.03, I 2 = 0% for heterogeneity, P = 0.81; Figure 2C).…”
Section: Resultsmentioning
confidence: 99%
“…In this meta-analysis, postoperative outcomes included the time to bowel functional recovery, time to start diet, length of postoperative hospital stay, and postoperative complications. Five studies reported the time to bowel functional recovery in 222 patients[23,24,26,30,31]. The pooled mean time to bowel functional recovery was shorter in the MIS group than in the OS group (WMD = -0.88 d, 95%CI: -1.58 to -0.19, P = 0.01, I 2 = 94% for heterogeneity, P < 0.00001; Figure 2D).…”
Section: Resultsmentioning
confidence: 99%